Selection criteria for Islamic home financing case study : customers of Bank Islam Malaysia Berhad / Siti Fairuz Che Pin ... [et al.] - Che Pin, Siti Fairuz; Ali, Nurulhuda; Senawi, Asma; Zainuddin, Ashrof (2012)
Of Man’s most basic needs, shelter is the most expensive, especially if he chooses to live in an urban environment. To obtain long term loans, borrowers must possess some measures of credit worthiness thus limits the number who can afford to pay for a house. Nowadays, there are many financial institution that offer housing loans. However, each financial institutions are varies in terms of the types of loan as well as the lending rate. In lieu of the rapid and massive development especially the residential houses have resulted to the tremendous increment of the number of housing loans being offered by financial institutions. Besides Middle East countries, Malaysia has been one of the famous financial centres for Islamic finance. Amongst the financial institutions in Malaysia, Bank Islam Malaysia Berhad (BIMB) has been of the earlier pioneer for Islamic financing as an alternative from existing conventional banking. The main objective of this research was to find out the top five choice criterions for Islamic home financing among Bank Islam Malaysia Berhad customers in Kuala Lumpur.